Analisis Framing Tirto.Id dan Kumparan pada Pemberitaan Kasus Ujaran Kebencian Habib Bahar - Siti Nursanti; Achmad Muayad; Mayasari (Universitas Serang Raya, 2020)
This study aims to find out and describe how the frame structure was formed by Tirto.Id and Kumparan online media in reporting Habib Bahar bin Smith's speech cases to President Joko Widodo. The analytical method used is framing analysis according to Pan Zhongdang and Gerald M. Kosicki. The results of this study indicate, based on an analysis of the syntactic structure, Tirto.Id and Kumparan want to look neutral or impartial. Rhetorical structure, both Tirto.Id and Kumparan emphasized that Habib Bahar was guilty, besides that Tirto.Id encouraged the Police to resolve this case objectively and indiscriminately, while Kumparan was seen trying to accentuate the life of Habib Bahar. In Script structure, both of these media both lack the completeness of script elements (5W + H) in several news articles posted. From the thematic structure, the themes related to the information conveyed by Kumparan appear to be wider than Tirto.Id, this is evidenced by the greater reporting portion. However, judging from the writing of information, Tirto.Id looks more skilled than Kumparan, Tirto.id writes and compiles information in a coherent and neat manner. Keywords: Framing Analysis, Kumparan, Online Media, Tirto.Id, Hate Speech